An interesting manifestation of COVID-19 in children: case report and review on multisystem inflammatory syndrome in pediatric patients - Sharmila Pendyala; Maqsood, Maryam; Vamsi Krishna Kaza (International Journal of Contemporary Pediatrics, 2023)
Multisystem inflammatory syndrome in children (MIS-C) associated with COVID-19 or PIMS-TS (pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 infection) has been presenting itself in children in connection to the SARS-CoV-2 infection. Along with a brief review of global data on MIS-C, we present two case reports of critically ill pediatric patients (aged 16 and 14 years), presenting with features of MIS-C from May 2020 to March 2021, to a tertiary-care hospital in Telangana, India. The patients with MIS-C were healthy prior to testing positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Clinical presentations were similar, with fever, abdominal pain, gastrointestinal complaints, or maculopapular rash. The diagnostic parameters revealed elevated levels of C-reactive protein, D-dimer, and NtProBNP. Other infectious aetiologies were ruled out. Both patients required ionotropic support, and intravenous immunoglobulin (IVIG), and were also given empiric antibiotics. Both were hemodynamically stable upon discharge. As knowledge of the various COVID-19 manifestations in children increases, reporting is essential to better-educating healthcare professionals in clarifying and streamlining the variety of symptoms connected to MIS-C and assessing the associated risk factors that predispose the pediatric population to develop severe disease.